Health care professionals' views on psychological factors affecting nutritional behaviour in people with motor neuron disease: A thematic analysis. Issue 4 (26th August 2019) - Zarotti, Nicolò; Coates, Elizabeth; McGeachan, Alex; Williams, Isobel; Beever, Daniel; Hackney, Gemma; Norman, Paul; Stavroulakis, Theocharis; White, David; White, Sean; Halliday, Vanessa; McDermott, Christopher; et al.
Abstract : Motor neuron disease (MND), also known as amyotrophic lateral sclerosis, is a neurodegenerative disorder that causes progressive muscle paralysis and typically leads to death within 3 years. As no cure is currently available, symptomatic management is the mainstay of treatment. An important part of this is optimizing nutritional intake with evidence that this may positively affect survival and quality of life. Health care professionals (HCPs) play a pivotal role in nutritional management of people with MND (pwMND) but, to date, their views on the psychological barriers faced by pwMND have not been explored. Such an exploration may identify ways in which the delivery of nutritional care for pwMND can be optimized. Methods: Five qualitative focus groups were carried out across the United Kingdom in June 2018 with 51 participants, including 47 HCPs involved with MND care and four service user representatives. Data were analysed through thematic analysis. Results: Four overarching themes were identified: psychological adjustment and patient engagement; nutrition and the need for control; knowledge of nutrition and the complexity of MND; and the psychosocial nature of eating. Conclusions: The findings suggest that the nutritional management of pwMND should be mindful of factors such as the impact of distress at the time of diagnosis, the availability of clear information on nutrition and MND, as well as the importance of illness perceptions and coping strategies. Moreover, tailored psychological interventions should be considered to mitigate the impact on MND on the experience of eating. Statement of contribution What is already known on this subject? Since weight loss and reduced body mass index (BMI) have been identified as independent risk factors for prognosis and survival in motor neuron disease (MND), nutritional management represents an important component of the symptomatic care of people with MND (pwMND) aimed at prolonging survival and maintaining or improving quality of life. However, the current guidelines and quantitative and qualitative literature on the topic are mainly focused on issues around enteral feeding and gastrostomy insertion, and very little is currently known about potential psychological enablers or barriers to earlier nutritional management, especially from the perspectives of health care professionals (HCPs) involved in the delivery of nutritional care in pwMND. What does this study add? First qualitative investigation of enablers or barriers to nutritional care in pwMND from the perspective of HCPs. New insight into psychological factors (e.g., adjustment, avoidance, loss of control) in nutritional care for pwMND. Practical implications and novel clinical suggestions for HCPs involved in nutritional care of pwMND.